Photocatalytic removal of methylene blue by bismuth vanadate prepared via polyol route - Moey, Melanie Hui Jia (2012)
In this study, visible-light driven photocatalyst BiVO4 was synthesized via polyol route. The effect of calcination temperature and duration on the characteristics of the resulting BiVO4 catalyst was studied by performing Thermogravimetric Analysis (TGA), X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), surface area measurement (BET method) and Diffuse Reflectance Spectroscopy (DRS). XRD analysis showed that monoclinic scheelite BiVO4 can be obtained by calcining the sample at 450 °C for 3 hours. The BiVO4 produced was olive-like in shape. The morphology of synthesized BiVO4 retained the same upon increasing the calcination temperature and duration. However, its surface area decreased and showed increment in its particle size when calcination temperature and duration increased. Calcination temperature and duration did not affect the band gap energy of the BiVO4 catalyst. The efficiency of resulted BiVO4 as a visible-light driven photocatalyst was examined by removing Methylene Blue (MB) dye from aqueous solution. The effect of operational parameters such as catalyst dosage, initial concentration of dye and initial pH of solution on the removal of MB was also studied. The removal percentage of MB increased with increasing mass up to an optimum mass of 0.6003 g. Rate of reaction increased with increasing initial concentration of MB. Highest removal percentage of MB was also achieved at its natural state of pH. Further, experimental design methodology was used for response surface modelling and optimisation of MB removal. A multivariate experimental design was employed to investigate its interaction relationship among catalyst loading, initial concentration of dye and initial pH of solution. The maximum removal percentage of MB approached 67.21 % under optimised conditions of 0.57 g BiVO4, 10.47 ppm of MB and at pH 4.7. A satisfactory goodness-of-fit was achieved between the predictive and the experimental results which indicates response surface methodology is a reliable tool for optimising removal percentage of MB.